PAIN AND SUFFERING AS AN EXISTENTIAL CHALLENGE: BETWEEN PHILOSOPHY AND THEOLOGY - Chuprin, Kyrylo (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2025)
Pain and suffering, as universal facets of human existence, permeate individual and collective experiences, prompting profound reflection on the meaning of being. In today’s world, marked by global crises, particularly the war in Ukraine, these phenomena acquire new dimensions, evolving beyond psychophysiological states into ontological challenges that shape human subjectivity. This study focuses on exploring the transformative potential of suffering through a synthesis of philosophical and theological perspectives, viewing it as a catalyst for ethical and mental growth. Its relevance arises from the urgent need to reconsider pain in the context of wartime traumas, which intensify existential questions, and the technological era, which reduces suffering to a mere functional issue, stripping it of her ontological depth. The works of S. Kierkegaard, M. Heidegger, V. Frankl, alongside recent studies by F. Mijatović and M. Burley underscore suffering as a boundary experience that unveils the authenticity of being. However, there is a lack of interdisciplinary approaches integrating philosophical and religious studies analyses with a focus on the Ukrainian context, where war amplifies the collective dimension of pain. The research aims to elucidate how suffering fosters the creation of new meanings by examining existential concepts, theological interpretations in Christianity, Buddhism, Islam, and Judaism, and the impact of digital culture on the perception of suffering. Special emphasis is placed on Ukraine’s wartime experience, where pain serves as a source of societal solidarity and ethical revaluation of values. The novelty of the study lies in its interdisciplinary synthesis, combining philosophical reflection with religious studies analysis to offer a holistic framework for understanding suffering as a source of spiritual and ethical meanings in crisis conditions. The findings demonstrate that suffering, despite its destructive nature, opens pathways for ontological rethinking of existence, fostering individual and collective resilience. The study also highlights the tension between the technological devaluation of pain and its existential significance, proposing ways to preserve the depth of human experience.